2020
DOI: 10.1002/pssa.201900963
|View full text |Cite
|
Sign up to set email alerts
|

Etching Asymmetric Germanium Membranes with Hydrogen Peroxide for High‐Capacity Lithium‐Ion Battery Anodes

Abstract: Germanium (Ge) is deemed as one of the most promising alloying anodes for rechargeable lithium‐ion batteries (LIBs) due to its large theoretical capacity, high electrical conductivity, fast lithium‐ion diffusivity, and mechanical robustness. However, Ge‐based anodes suffer from large volume changes during lithiation and delithiation, which can deteriorate their electrochemical performance rapidly. Herein, the large volume change issue is effectively addressed using an asymmetric membrane structure that is prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Quite a few strategies have been proposed to accommodate the large volume change of antimony-based alloy anodes, most of which focus on nano-structuring, compositing, alloying, as well as developing new binders and electrolyte additives [10,[13][14][15]. Recently, asymmetric membrane structure has been adopted by our laboratory for the first time to alleviate the severe volume expansion of highcapacity anodes in LIBs, such as Si, Ge and Sn nano/micron particles [16][17][18][19][20][21]. In this study, antimony nanobelts embedded in carbonaceous asymmetric membranes are synthesized, characterized and employed as the alloy anode material for high capacity/performance SIBs.…”
Section: Nasb 2na 2ementioning
confidence: 99%
“…Quite a few strategies have been proposed to accommodate the large volume change of antimony-based alloy anodes, most of which focus on nano-structuring, compositing, alloying, as well as developing new binders and electrolyte additives [10,[13][14][15]. Recently, asymmetric membrane structure has been adopted by our laboratory for the first time to alleviate the severe volume expansion of highcapacity anodes in LIBs, such as Si, Ge and Sn nano/micron particles [16][17][18][19][20][21]. In this study, antimony nanobelts embedded in carbonaceous asymmetric membranes are synthesized, characterized and employed as the alloy anode material for high capacity/performance SIBs.…”
Section: Nasb 2na 2ementioning
confidence: 99%
“…Therefore, tremendous effort has been made to explore the fundamental basics of high-capacity and high-energy electrode materials and many strategies have been proposed to conquer the obstacles of boosting energy density of the batteries. One strategy is to reduce particle size to nanoscale to alleviate mechanical strain. For example, Liu et al found that, during the first lithiation process, the nanoparticles with diameters less than 150 nm undergo volume expansion without fracturing or cracking, suggesting that nanoparticles can tolerate huge volume change .…”
Section: Corn-mediated Carbonaceous Host Matrixes For High-capacity E...mentioning
confidence: 99%
“…22 Therefore, to meet the production and market demand for energy storage devices, micron-sized red phosphorus with high cycling stability are eagerly expected for practical application. 23,24 To this end, structural design and material engineering are regarded as an effective strategy to accommodate the intrinsic obstacles of RP. In various structures, the porous structure has been extensively designed in nanomaterials, as it owns a large amount of free pores, so its inward expansion could effectively buffer the particle-level volume change of the whole particle during cycling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when the active particles are reduced to nanometer size, the bulk packing density and stability will be compromised, and the energy consumption and cost will be greatly increased . Therefore, to meet the production and market demand for energy storage devices, micron-sized red phosphorus with high cycling stability are eagerly expected for practical application. , …”
Section: Introductionmentioning
confidence: 99%